2012
DOI: 10.3324/haematol.2012.069328
|View full text |Cite
|
Sign up to set email alerts
|

Lenalidomide as salvage treatment for multiple myeloma relapsing after allogeneic hematopoietic stem cell transplantation: a report from the French Society of Bone Marrow and Cellular Therapy

Abstract: ABSTRACTseries of 52 allografted MM patients who received lenalidomide for post-transplant relapse. We show that, in this setting, the use of lenalidomide is feasible and induces high response rates, at least in part due to its immunomodulatory effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
26
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 23 publications
4
26
0
Order By: Relevance
“…These data confirm those reported in previous smaller series and suggest that lenalidomide has higher efficacy compared with thalidomide, comparable to that of bortezomib. 12 The toxicity profile of the treatment was in line with that reported in previous studies and led to dose reductions and treatment interruption in 44% and 17% of patients, respectively.…”
supporting
confidence: 73%
See 2 more Smart Citations
“…These data confirm those reported in previous smaller series and suggest that lenalidomide has higher efficacy compared with thalidomide, comparable to that of bortezomib. 12 The toxicity profile of the treatment was in line with that reported in previous studies and led to dose reductions and treatment interruption in 44% and 17% of patients, respectively.…”
supporting
confidence: 73%
“…[8][9][10][11] In the current issue of the Journal, three interesting papers have been published evaluating the role of lenalidomide alone or in combination with steroids and alkylating agents in three different settings of patients with plasma cell dyscrasia. [12][13][14] Coman et al presented the results of a retrospective multicenter study on MM patients receiving lenalidomide alone or in combination with dexamethasone as salvage therapy after allo-SCT. 12 This study is the largest reported in this setting.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…On LEN therapy, 31% developed or exacerbated an acute GVHD episode, which was significantly associated with an improved antimyeloma response; however, at least one death was attributed to GVHD. 71 The feasibility of LEN maintenance after allotransplant has been evaluated prospectively. The HOVON-76 trial assessed LEN maintenance starting 1 to 6 months after allotransplant for newly diagnosed MM.…”
Section: Donor Lymphocyte Infusionmentioning
confidence: 99%
“…[2][3][4][5] Lenalidomide has also been shown to increase the activity of GVHD, which may manifest as isolated liver involvement. [6][7][8][9] Pomalidomide was approved in February 2013 for use in treating refractory plasma cell myeloma, and toxicities involving the hepatobiliary system were not frequently seen nor reported in preclinical and clinical studies leading to its FDA approval. 10 We report on a patient who developed a biopsy-proven hepatic necrosis associated with the initiation of pomalidomide after allo-HCT, which resolved on discontinuation of pomalidomide.…”
mentioning
confidence: 99%